2019
DOI: 10.1177/1076029619841700
|View full text |Cite
|
Sign up to set email alerts
|

Primary Thrombophilia in Mexico XIII: Localization of the Thrombotic Events in Mexican Mestizos With the Sticky Platelet Syndrome

Abstract: The sticky platelet syndrome (SPS) is a common cause of both arterial and venous thrombosis, being a dominant autosomal disease with qualitative platelet alterations and familial occurrence. It is characterized by platelet hyperreactivity with increased platelet aggregability in response to low concentrations of platelet agonists: epinephrine, adenosine diphosphate, or both. The clinical manifestations involve venous or arterial thrombosis, recurrent pregnancy loss, and fetal growth retardation. To analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…As a result of our interest in the SPS and with the assistance of various collaborators and of the previously mentioned giant clotters, we have now pieced several features of the SPS which can be summarized as follows [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] :…”
Section: La Troisième…mentioning
confidence: 99%
“…As a result of our interest in the SPS and with the assistance of various collaborators and of the previously mentioned giant clotters, we have now pieced several features of the SPS which can be summarized as follows [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] :…”
Section: La Troisième…mentioning
confidence: 99%
“…As a result of our interest in the SPS and with the assistance of various collaborators and of the previously mentioned giant clotters, we have now pieced several features of the SPS which can be summarized as follows 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 :…”
Section: La Troisième…mentioning
confidence: 99%
“…Caucasians suffer from SPS type II more frequently [ 20 ], whereas type I is more frequently seen in Mexican Mestizos. SPS is also the second most common cause of thrombophilia in this ethnic group [ 21 ]. We also conducted a study to define the identification of SPS worldwide and found that patients with the condition have been identified and reported in the five continents [ 12 ].…”
Section: Introductionmentioning
confidence: 99%